2019
DOI: 10.3390/ijms20236043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Brushing on Deflection, Maximum Load, and Wear of Stainless Steel Wires and Conventional and Spot Bonded Fiber-Reinforced Composites

Abstract: Fiber-reinforced composite (FRC) retainers are an aesthetic alternative to conventional Stainless Steel splints. They are generally used with a full bonded technique, but some studies demonstrated that they could be managed with a spot bonding technique to significantly decrease their rigidity. In order to propose this FRC spot bonding technique for clinical use, the aim of this study was to evaluate mechanical properties and surface wear of fibers left uncovered. Tests were made by simulating tooth brushing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The load value in N with the predetermined magnitude of deflection was used as a descriptive value of the retainer´s rigidity. The highest values of maximum load were reported for FRC covered specimens (conventional technique), and these results confirm previous studies [21,22,29] which demonstrated the higher rigidity of fully covered FRC frameworks if compared to the metal ones. Uncovered FRCs showed lower values, as reported in previous studies [24,25].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The load value in N with the predetermined magnitude of deflection was used as a descriptive value of the retainer´s rigidity. The highest values of maximum load were reported for FRC covered specimens (conventional technique), and these results confirm previous studies [21,22,29] which demonstrated the higher rigidity of fully covered FRC frameworks if compared to the metal ones. Uncovered FRCs showed lower values, as reported in previous studies [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…In this report stainless steel specimens were tested before tooth brushing, after 26 min, and after 60 min of tooth brushing: no significant difference was shown both for maximum load and for maximum bending stress. Conversely, a significant reduction of maximum load values was reported in a previous study [29], but the reduction of values after tooth brushing were due to the wear composite used to fix the wires. Therefore, tooth brushing does not damage metal wires.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations